Estimation of building energy performance for local energy policy at urban scale. (September 2017) - Belussi, Lorenzo; Danza, Ludovico; Ghellere, Matteo; Guazzi, Giulia; Meroni, Italo; Salamone, Francesco
Abstract: Cities play a key role in sustainability policies aimed at reducing environmental impacts and increasing energy efficiency in the building sector. At urban level, the analysis models are split in bottom-up and top-down types as a function of the methodological approach of input data processing, aggregated in the first case and disaggregated in the second one. The present paper describes the methodological approach adopted for the implementation of a bottom-up model able to estimate the energy performance of buildings and to define an energy diagnosis process at urban scale. Starting from the information provided by tools available at the Public Authorities and at the most relevant statistical studies on the national energy market, the model provides an estimation of the energy consumption and performance of buildings. The model is applied to a real district of Bologna and the derived spatial database allows the energy performances of buildings to be mapped.